Inflammatory Bowel Disease and Colorectal Cancer: An Eternal Fire in a Beautiful Garden - Koyyala, Venkata Pradeep Babu; Kantharia, Chetan; Darooka, Naitica; Kumar, Mandhir; Ranjan, Piyush; Anikhindi, Shrihari; Bansal, Naresh Kumar; Sharma, Praveen; Bhalla, Dr. V.P.; Kumar, Manish; Sharma, Mohit; Abrol, Deepak; Sahni, Peush; Ardhanari, Ramesh; Pradeep, R.; Yadav, Amitabh; John, Suviraj; Rawat, Saumitra; Parikh, Purvish; Selvasekar, C.; Aggarwal, Shyam (South Asian Journal of Cancer, 2024)
Inflammatory bowel disease (IBD), encompassing Crohn's disease and ulcerative colitis, significantly increases the risk of colitis-associated cancer (CAC). Chronic inflammation, a key contributor to carcinogenesis, disrupts immune surveillance, induces deoxyribonucleic acid (DNA) damage, and alters genetic and epigenetic pathways. Molecular pathways such as STAT3, mTOR, and NF-κB drive CAC progression, while unique microbiome alterations—loss of Faecalibacterium prausnitzii and increases in Escherichia coli and Fusobacterium species—exacerbate the inflammatory milieu. CAC accounts for 2% of all colon cancers and up to 15% of IBD-related deaths. Risk correlates with IBD duration, increasing approximately 1% annually after the first decade. Surveillance via colonoscopy is crucial, with chromoendoscopy recommended for high-risk cases. Preventive drugs, including aminosalicylates, thiopurines, and biologics, offer modest benefits but lack conclusive evidence. Post-CAC diagnosis, immunosuppressants are discontinued in favor of corticosteroids, with 5-aminosalicylates continued as needed. The use of immune checkpoint inhibitors remains controversial due to exacerbation of colitis. Emerging insights into the gut microbiota's role in IBD and CAC may revolutionize prevention and management strategies. Advances in screening, surveillance, and therapeutic approaches have reduced CAC mortality, underscoring the importance of personalized medicine and ongoing research to address these complex conditions.
Keywords: hereditary risk; immune deficiency; cytokine; precancerous